2022
DOI: 10.3390/nu14102129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutrition and Exercise on Body Composition, Exercise Capacity, and Physical Functioning in Advanced CKD Patients

Abstract: Patients with stages 4 and 5 chronic kidney disease (CKD), and particularly chronic dialysis patients, commonly are found to have substantially reduced daily physical activity in comparison to age- and sex-matched normal adults. This reduction in physical activity is associated with a major decrease in physical exercise capacity and physical performance. The CKD patients are often physically deconditioned, and protein energy wasting (PEW) and frailty are commonly present. These disorders are of major concern b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…These results also suggest that TRF may lead to too much reduction in CKD patient intakes. Reduced protein intake may lead to sarcopenia, decreasing muscle strength, which in turn could lead to disease progression and increased mortality ( 49 ). Therefore, TRF should be accompanied by as much exercise as possible for patients to maintain muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that TRF may lead to too much reduction in CKD patient intakes. Reduced protein intake may lead to sarcopenia, decreasing muscle strength, which in turn could lead to disease progression and increased mortality ( 49 ). Therefore, TRF should be accompanied by as much exercise as possible for patients to maintain muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins and amino acids enter the bloodstream and stimulate an increase in the inflammatory response, which can promote tumor growth and metastasis ( 57 , 58 ). Second, muscle wasting leads to decreased nutrient uptake and metabolic capacity ( 59 ). Muscle tissue has high energy and nutrient demands, and when muscle wasting occurs, the body’s metabolic rate and energy expenditure also decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, muscle tissue can break down protein to produce amino acids, which are essential building blocks for protein synthesis and cellular function. Muscle wasting can therefore result in amino acid deficiency, which can further affect tumor cell growth and division ( 59 , 60 ). Third, muscle wasting leads to decreased immune function ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, it might be difficult to expect changes in strength or body composition, without offering exercise and nutritional intervention. Previous studies on HD patients showed improvement in strength and muscle mass when patients followed an exercise program [ 49 ]. No difference was found in daily activities measured with PAM or LAPAQ, although our data did show that 6 patients in the NHD group started with exercise activities in comparison with 1 CHD patient during our study.…”
Section: Discussionmentioning
confidence: 99%